PENERAPAN STRATEGI NABI IBRAHIM DALAM MENDIDIK ANAK DALAM TAFSIR SURAT ASH-SHAFFAT AYAT 99-113 (Studi Kasus di Madrasah Tsanawiyah 3 Muhammadiyah Masaran Sragen) - Sahirman, Sahirman (Universitas Muhammadiyah Surakarta, 2014)
This study intends to examine the problems of quality and education value to the children, reviewing the events of the dream with the prophet Abraham to slayhis son Ishmael alaihimas greetings in Q.S Ash-Shaaffaat: 99-113. The problem in thisstudy are, 1) what strategies are used to educate children of Abraham in the SurahAsh-Shaaffaat: 99-113? 2) The value of what you want to be grown by the prophetIbrahim strategies in educating children contained in surah Ash-Shaaffaat: 99-113? 3) What is the relevance of the strategy developed by prophet Ibrahim in Surah Ash-Shaaffaat: 99-113 on Islamic education curriculum in MTs.3 Muhammadiyah MasaranSragen? This is qualitative study which refers to the data of scientific papers (researchlibrary), the approach used is a model of thematic tafsir (maudhu?i), the data collectiontechniques are document study, while analyzing the data used in the content analysis (content analysis). Inductive method is used to infer from the data that has been analyzed previously, are then described in words. The results of this study suggest that strategies to educate children of Abraham are: purification of the soul, are in a good environmentand controlled, has a vision, mission and goals, have excellent communication, has aspirit of sacrifice to achieve the contentment, love and help of god, has the formula ?aljaza? min jinsil charity?. The resulting values are: a lot of praying, establish the prayer, has the power embroidery, Honesty, Patience and have responsibility. Abraham and education strategy as far as the authors are very relevant to the study of Islamic educationcurriculum in MTs.3 Muhammadiyah Masaran Sragen Academic Year 2009/2010.Keywords: strategy; education; child.Penelitian ini bermaksud meneliti masalah kualitas dan nilai pendidikan padaanak, dengan mengkaji peristiwa mimpi Nabi Ibrahim untuk menyembelih anaknyaIsmail alaihimas salam dalam Q.S Ash-Shaaffaat: 99-113. Permasalahan dalampenelitian ini adalah: pertama, apa strategi yang digunakan Nabi Ibrahim dalammendidik anak dalam Q.S Ash-Shaaffaat: 99-113? Kedua, nilai apa yang inginditumbuhkan dengan strategi yang dilakukan Nabi Ibrahim dalam mendidik anak yangterdapat dalam Q.S Ash-Shaaffaat: 99-113? Ketiga, Bagaimana relevansi strategi yangdikembangkan oleh Nabi Ibrahim dalam Q.S Ash-Shaaffaat: 99-113 pada kurikulumpendidikan agama Islam di MTs.3 Muhammadiyah Masaran Sragen? Penelitianini bersifat kualitatif yang mengacu pada data-data karya ilmiah (library research),pendekatan yang digunakan adalah ilmu tafsir model tematik (maudhu?i), Teknikpengumpulan data adalah dokumentasi, sedangkan dalam menganalis datadigunakan analisis isi (conten analysis). Metode induktif digunakan untukmengambil kesimpulan dari data-data yang telah dianalisis sebelumnya, yangkemudian dijelaskan dengan kata-kata. Hasil dari penelitian ini menunjukkanbahwa strategi Nabi Ibrahim dalam mendidik anak adalah: pensucian jiwa, beradapada lingkungan yang baik dan terkontrol, memiliki visi misi dan tujuan, memilikikomunikasi yang excellent, memiliki semangat berkorban untuk meraih keridhaan, kecintaan dan pertolongan Allah, memiliki rumus ?al-jaza? min jinsil amal?.Strategi pendidikan Nabi Ibrahim sejauh penelitian penulis sangat relevan dengankurikulum pendidikan agama Islam di MTs. 3 Muhammadiyah Masaran SragenTahun Ajaran 2009/2010Kata Kunci: strategi; pendidikan; anak.